Managing corporate Waqf in Malaysia: perspective of selected SEDCs and SIRCs - Md Saad, Norma; Mhd. Sarif, Suhaimi; Osman@Hussin, Ahmad Zamri; Hamid, Zarinah; Saleem, Muhammad Yusuf (Akademi of Islamic Studies, Universiti Malaya, 2017)
Waqf is described as an act of dedicating a corpus of property or financial assets in perpetuity for the cause of Allah SWT. The ownership of the property or assets are transferred to Allah SWT but the benefits are dedicated to the poor, sick, marginalized segment of the society, or any other virtuous causes. Waqf institutions are among several instruments instituted by Islam to combat poverty and enhance welfare in the society. Waqf provides the material infrastructure and creates a source of revenue for use in, among others, social welfare enhancing activities both at family, community and state levels. Corporate waqf is defined as a type of waqf where the mawquf (waqf assets) are in the form of shares issued and managed by a corporate entity. Corporate waqf utilizes the application of waqf principles in a corporate setting (Islamic-finance/c/corporate-waqf.html).Corporate waqaf is more than a charitable and philanthropic act by a business entity. It is an initiative to combine waqaf concept and apply it to achieve business and corporate objectives. Corporate waqaf, consequently, intends to redefine the role and function of business organizations in today’s society by ‘giving back’ to the society and reaching out to the community. This study tries to gauge the level of awareness and willingness State Economic Development Corporations (SEDCs) and State Islamic Religious Councils (SIRCs) to be involved in corporate waqaf initiatives. The study found that, in general, the SEDCs are receptive of the idea of corporate waqf entities managing and enhancing the values of waqf assets and waqf properties, however, this must be done within the current legal framework. The study also found that there is lack of coordination between the SEDCs and SIRCs in making decisions on matters related to waqf. It is suggested that the state government, through its departments/agencies, play facilitative role in ensuring that the processes of the development of waqf assets/properties are done in an efficient manner.